1991
DOI: 10.1002/ajh.2830380206
|View full text |Cite
|
Sign up to set email alerts
|

Increased response of erythroid progenitors to interleukin‐3 in sickle cell anemia: CFU‐E‐like behavior of circulating erythroid progenitors in liquid culture

Abstract: Erythroid progenitors circulating in peripheral blood and their response to erythropoietin (EPO), interleukin-3 (IL3), and phytohemagglutinin-stimulated, lymphocyte-conditioned medium (PHALCM) were assessed in sickle cell anemia (SCA) patients and controls. SCA patients have significantly higher numbers of circulating burst-forming unit-erythroid (BFU-E) compared with controls (mean +/- SEM, 940.27 +/- 129.11 per ml and 86.56 +/- 19.74 per ml, respectively; P less than 0.0001). At low doses of EPO, BFU-E-deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The only common feature in all these diseases that could explain this similarity is the increased sensitivity to Epo [4,6,10,18,20,24]. Epo hypersensitivity in SS as well as ␤ thalassemic patients has been demonstrated by several authors [4,5,8,10] using Epo dose-response curves. These findings demonstrate considerable colony formation at low Epo concentrations, when compared with control subjects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The only common feature in all these diseases that could explain this similarity is the increased sensitivity to Epo [4,6,10,18,20,24]. Epo hypersensitivity in SS as well as ␤ thalassemic patients has been demonstrated by several authors [4,5,8,10] using Epo dose-response curves. These findings demonstrate considerable colony formation at low Epo concentrations, when compared with control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that this Epo hypersensitivity may occur as a result of changes in the erythroid progenitors such as increased numbers of Epo receptors, increased accessibility of otherwise cryptic receptors, activation or change in the affinity of the receptors for the ligand on the surface of the progenitor cells, and/or altered Epo signal transduction pathway [5,[35][36][37][38][39]. Thus, it is possible that this Epo hypersensitivity may occur as a result of changes in the erythroid progenitors such as increased numbers of Epo receptors, increased accessibility of otherwise cryptic receptors, activation or change in the affinity of the receptors for the ligand on the surface of the progenitor cells, and/or altered Epo signal transduction pathway [5,[35][36][37][38][39].…”
Section: Fig 2 Numbers Of Early Circulating Erythroid Progenitor Cementioning
confidence: 99%
See 1 more Smart Citation
“…They often have increased levels of Hb F, which if sufficiently high may lead to some modulation of clinical symptoms. It is well documented that SS [3][4][5][6][7] and ␤ thalassemic [6,8,9] patients have a higher than normal number of circulating BFU-E. It was demonstrated further that these progenitors expressed hypersensitivity to erythropoietin (Epo) [4,8,10].…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated further that these progenitors expressed hypersensitivity to erythropoietin (Epo) [4,8,10]. In addition, some authors have observed the formation of spontaneous BFU-E colonies (without stimulus) in SS patients [5]. This finding is of particular interest because spontaneous BFU-E colony formation (autoproliferation) is generally thought to be a characteristic feature of myeloproliferative disorders such as polycythemia vera, which is associated with abnormal expansion of erythroid stem cell clones.…”
Section: Introductionmentioning
confidence: 99%